Effective Dosage of Ciprofol for the Induction of General Anesthesia Across Diverse Age Groups in Adults: A Single-Center, Prospective, Non-Randomized Sequential Trial - Deng L; Zhang C; Tan M; Zeng W; Luo G; Li P (Journal of Pain Research)
Lizhen Deng,* Chunyuan Zhang,* Meiyun Tan, Wei Zeng, Guozhan Luo, Ping Li Department of Anesthesiology, Affiliated Boai Hospital of Zhongshan, Zhongshan, Guangdong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Meiyun Tan, Department of Anesthesiology, Affiliated Boai Hospital of Zhongshan, No. 6 Chenggui Road, East District, Zhongshan, Guangdong, 528400, People’s Republic of China, Tel +86-13726028414, Email 13726028414@163.comPurpose: A new Chinese-developed intravenous anesthetic called ciprofol enhances propofol’s effectiveness against GABAA receptors by adding cyclopropyl. This study aims to determine the optimal dosage of ciprofol for inducing general anesthesia in adult patients of different ages and its correlation with Narcotrend index (NTI).Patients and Methods: 105 patients were stratified into three age groups: 18– 40 (Group A), 41– 65 (Group B), and 66– 85 (Group C) years. Initial doses of 0.4 mg/kg (Groups A and B) and 0.3 mg/kg (Group C) ciprofol tosilate were administered, adjusted by 0.05 mg/kg based on sedation efficacy. The Modified Observer’s Assessment of Alertness/Sedation (MOAA/S) scale and Dixon up-and-down method were used to calculate ED50, ED95, and NTI50.Results: Effective dosages were: youth (ED50=0.526 mg/kg, ED95=0.610 mg/kg), middle-aged (ED50=0.366 mg/kg, ED95=0.450 mg/kg), and elderly (ED50=0.324 mg/kg, ED95=0.408 mg/kg). NTI50 were 38.068 (33.496– 44.188), 44.963 (39.311– 52.270), and 47.214 (39.792– 57.420) for the three groups, respectively.Conclusion: Ciprofol is safe and effective for anesthesia induction across age groups, with lower doses required for elderly patients. NTI reduction was dose-dependent and slower in elderly patients.Keywords: ciprofol, anesthesia induction, optimal dose, adult, sequential allocation